7x+4=(x+3)+(8x-9)

Simple and best practice solution for 7x+4=(x+3)+(8x-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+4=(x+3)+(8x-9) equation:



7x+4=(x+3)+(8x-9)
We move all terms to the left:
7x+4-((x+3)+(8x-9))=0
We calculate terms in parentheses: -((x+3)+(8x-9)), so:
(x+3)+(8x-9)
We get rid of parentheses
x+8x+3-9
We add all the numbers together, and all the variables
9x-6
Back to the equation:
-(9x-6)
We get rid of parentheses
7x-9x+6+4=0
We add all the numbers together, and all the variables
-2x+10=0
We move all terms containing x to the left, all other terms to the right
-2x=-10
x=-10/-2
x=+5

You can always share this solution

See similar equations:

| 6(x+8)-2(-15+4)=31 | | 7a/3+4=18 | | 5x+2=27+(3x-1) | | 5m+7=34 | | 2x+72=98 | | 12x+2(x+8)+6=8-(-4x+6) | | 4x-60=40 | | 86+6x-60+2x=50 | | X=0,y=2 | | 4x-16+14+6=62 | | 2x+3=24-x | | y²-y-6=0 | | 2x-3+2x-3=5x-12 | | 75=3(f-60) | | -9x=1-4-9 | | 5x=x+5/3x+7 | | 70=7(p+5) | | 21+7j=56 | | -10x+3=7x-3 | | (1/2)x+7=14 | | -8x-8x=1-4x-8x+7 | | 5x^-2x+5=0 | | 230g+57=3277 | | 42/m-5=1 | | 100÷30x=15x | | (71-9x)+12x=5 | | 32+y/12=36 | | 3(p-2)=-21 | | 5/6-x+2x/3=x+3/9 | | 5y-17=2y+1 | | 374x-8=86 | | 16=7+b/2 |

Equations solver categories